STUDY OF THE WORK OF AHMAD TABIBIY - Nurmamatova Aziza (International Journal of Literature and Language Studies, 2026)
This article examines the history of scholarly research on the life and literary legacy of Ahmad Tabibi, a prominent representative of the Khorezm literary milieu of the late nineteenth and early twentieth centuries. The study analyzes early biographical and descriptive accounts found in the works of contemporary tazkira writers such as Hasanmuradqori Laffasi and Muhammad Yusuf Bayani. Special attention is given to the evaluations of the Russian orientalist A. N. Samoylovich and the systematic studies conducted by Uzbek scholars including F. Gʻanikhojayev, M. Yunusov, V. Mirzayev, and G. Karimov. The article identifies the main directions, achievements, and limitations of previous research on Tabibi’s works and outlines key perspectives for further comprehensive investigation of his literary heritage.